Religião e parentesco na colônia Castrolanda - Rickli, João Frederico (Revista de Antropologia, 2004)
This article seeks to draw a systematic picture of the relations between religion and kinship in Castrolanda, a colony made up of dutch immigrants in the countryside of Paraná State. It describes some rituals of the local church and some aspects of kinship, like the division of the families in four generations, the criteria for this division, and the pattern of marriages and alliances inside every generation. Through these descriptions, the present text seeks to explain the relationship beetwen kinship and religion, supported by theoretical considerations such as the notion of maison and the notion of hierarchical encompassment.